2017
DOI: 10.1097/qai.0000000000001340
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mother–Infant Pair Clinics and Short-Text Messaging Service (SMS) Reminders on Retention of HIV-Infected Women and HIV-Exposed Infants in eMTCT Care in Malawi: A Cluster Randomized Trial

Abstract: MIP and MIP + SMS service delivery models were ineffective in improving maternal and infant retention in rural Malawi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 17 publications
3
50
0
Order By: Relevance
“…This study similarly reported improved ANC visit attendance . In contrast to the other studies, a study in Kenya that sent SMS reminders to CHW to facilitate tracking of mother and infant pairs who missed their scheduled clinic visits, found no improvement on maternal retention at 12 months postpartum (Mwapasa et al, 2017). Similarly, a study in South Africa that offered HIV-positive women during late pregnancy motivational text messages and phone calls through a case manager until first six weeks of delivery, also reported no difference in retention at 12 months postpartum (S R .…”
Section: Maternal Retentionmentioning
confidence: 60%
See 2 more Smart Citations
“…This study similarly reported improved ANC visit attendance . In contrast to the other studies, a study in Kenya that sent SMS reminders to CHW to facilitate tracking of mother and infant pairs who missed their scheduled clinic visits, found no improvement on maternal retention at 12 months postpartum (Mwapasa et al, 2017). Similarly, a study in South Africa that offered HIV-positive women during late pregnancy motivational text messages and phone calls through a case manager until first six weeks of delivery, also reported no difference in retention at 12 months postpartum (S R .…”
Section: Maternal Retentionmentioning
confidence: 60%
“…The studies differed in the types of outcome definitions but most interventions used SMS reminders either aimed at the patient or CHW. Six studies compared standard care with SMS and/or voice call combination interventions that included reminders, laboratory result notification or health promotion messages to improve maternal retention in the PMTCT continuum Finocchario-Kessler et al, 2014;Mushamiri, Luo, Iiams-Hauser, et al, 2015;Mwapasa et al, 2017;. One study in Kenya offered two-way text messaging and weekly calls to women during pregnancy and the postpartum period.…”
Section: Maternal Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss to follow-up of HIV-positive women and their children is a major problem threatening the global target of eliminating HIV mother-to-child transmission. This study was nested within a larger study assessing the effectiveness of integrating mother infant pair clinics and Short Message Service-based tracing of defaulting mothers in improving the retention of mother-infant pairs in HIV care 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an SMS messaging intervention was introduced to fast-track community volunteers' responses and tracing of women who did not attend clinic appointments. 10 Neither additional clinic staff nor financial incentives were offered as part of the intervention package. Based on a very strict study definition—attendance at 12 months postpartum and also attendance at every scheduled visit before then (±14 days)—rates of maternal retention at 12 months postpartum were only between 19% and 25% in any arm.…”
Section: Health Systems' Intervention and Retention In Care And Othermentioning
confidence: 99%